2016
DOI: 10.1002/ett.3129
|View full text |Cite
|
Sign up to set email alerts
|

Seek and decode: Random access with physical‐layer network coding and multiuser detection

Abstract: We present a novel cross layer approach to random access (RA) that combines physical-layer network coding (PLNC) with multiuser detection (MUD). PLNC and MUD are applied jointly at the physical level in order to extract any linear combination of messages experiencing a collision. The set of combinations extracted from a whole frame is then processed by the receiver to recover the original packets. A simple pre-coding stage at the transmitting terminals allows the receiver to further increase system diversity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is seen that the same NC is extracted for both methods. The proposed method in He and Liew 13 makes X R after 2 time slots using (1), while our proposed method extracts the same X R in 1 time slot based on PLNC-NWRC using (5). Considering Figure 2, the upper bound of probability of error for X R in He and Liew 13 can be calculated as follows:…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen that the same NC is extracted for both methods. The proposed method in He and Liew 13 makes X R after 2 time slots using (1), while our proposed method extracts the same X R in 1 time slot based on PLNC-NWRC using (5). Considering Figure 2, the upper bound of probability of error for X R in He and Liew 13 can be calculated as follows:…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The concept of physical layer network coding (PLNC) was introduced in Zhang et al, 1 which stimulated several research papers in this area, where, for example, some of them investigate code detection issues, [2][3][4][5] some issues related to synchronization analysis, 6 and some provide channel estimation methods in PLNC systems. [7][8][9][10] The basic idea of PLNC challenges the traditional treatment of interference in wireless networks as a destructive phenomenon, by utilizing the interference to increase the throughput.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the considered scheme combines the principles of (a) contention based random access to allow for access protocol with small signaling overhead; (b) non-orthogonal transmissions, that is, allowing multiple users to transmit simultaneously over the same physical resources to efficiently use the spectrum, and (c) channel coding features to efficiently deal with collisions and exploit code redundancy at frame level. The main focus has been to advance on practical aspects of the PHY/MAC components [3] to improve access connectivity in the framework of mMTC services requiring short packet transmissions. Packet length is therefore a relevant aspect of the study.…”
Section: Introductionmentioning
confidence: 99%
“…We shall remark that even though in this work we consider that the same payload is repeated in all packets transmission attempts by each user per frame (x k,1 = x k,2 ) a pre-coding consisting in a multiplication over the extended binary field can be applied [3] in a straightforward manner. Such extension, does not modify the PHY-layer procedure.…”
mentioning
confidence: 99%
“…If different users select the same time slot for transmission, a packet collision is experienced. While collided packets were irremediably lost in early versions of SA, recent studies have shown that collisions can be resolved by network diversity, multiuser detection, network coding strategies [3]- [5], or by successive interference cancellation (SIC) techniques [6] which substantially improves the system throughput. The key concept behind SIC is that each user might send repetitions of the same message in different slots.…”
Section: Introductionmentioning
confidence: 99%